2014
DOI: 10.1111/jep.12250
|View full text |Cite
|
Sign up to set email alerts
|

Patients' substantialization of disease, the hybrid symptom and metaphysical care

Abstract: In the context of current scholarship concerned with facilitating integration between the biomedical and the patient-centred models of care, the article suggests that disease brings about an ontological disruption in patients, which is not directly addressed in either model, and may interfere with treatment and therapy outcomes if not met with a type of care termed here as 'metaphysical'. The receipt of diagnosis and medical care can give patients the sense that they are ontologically diminished, or less of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Noting how easy it is for us to become depersonalized when we become patients, Mitchell argues (in line with contributors to previous editions of this journal) that we can be compliant in this depersonalization because “in the early stages, particularly of serious illness, we do not wish to face the fact that our body is failing.” Rather than face this, “we separate ourselves from our illness”: we do not take ourselves to the doctor for treatment, but rather we take our illness. Mitchell presents a compelling account of the “fragmentation” of the person that ensues, how health professionals and systems can push us in the direction of this depersonalization and also how we can regain the status of personhood while remaining users of the health care system.…”
Section: Person‐centred Care and The Phenomenology Of Illnessmentioning
confidence: 85%
See 1 more Smart Citation
“…Noting how easy it is for us to become depersonalized when we become patients, Mitchell argues (in line with contributors to previous editions of this journal) that we can be compliant in this depersonalization because “in the early stages, particularly of serious illness, we do not wish to face the fact that our body is failing.” Rather than face this, “we separate ourselves from our illness”: we do not take ourselves to the doctor for treatment, but rather we take our illness. Mitchell presents a compelling account of the “fragmentation” of the person that ensues, how health professionals and systems can push us in the direction of this depersonalization and also how we can regain the status of personhood while remaining users of the health care system.…”
Section: Person‐centred Care and The Phenomenology Of Illnessmentioning
confidence: 85%
“…Heidegger's account of the experience of anxiety and the way that separates us from "the world of involvements" is a crucial starting point for the paper which follows, focusing on the journey "from person to patient and back again." 50 Noting how easy it is for us to become depersonalized when we become patients, Mitchell argues (in line with contributors to previous editions of this journal 86,87 ) that we can be compliant in this depersonalization because "in the early stages, particularly of serious illness, we do not wish to face the fact that our body is failing." Rather than face this, "we separate ourselves from our illness": we do not take ourselves to the doctor for treatment, but rather we take our illness.…”
Section: Person-centred Care and The Phenomenology Of Illnessmentioning
confidence: 97%
“…A couple of times already I have argued that regardless what philosophical argument prevails and the theoretical position that the clinician adheres to, what is philosophically useful in the therapeutic practice of physicians and psychologists should receive separate consideration. Thus, that the human being is a substance, and diseases are not natural kinds can be contested, but I have shown that these views have value and utility for clinicians . In a similar line of thought, Fuller and Upshur caution that, whether the nature of the person as conceptualized in the person‐centred model of care is true to reality or a constructed version of it, matters less than does its instrumental role of influencing patient care .…”
Section: Monistic Dualism: the Ontology Of The Healthy Doctormentioning
confidence: 99%
“…The need to be explicit about underlying assumptions which frame our thinking about medical conditions is highlighted in the paper by Alexandra Parvan – although her concern is not primarily with the assumptions of physicians, nurses or family carers, but with the way that patients with chronic conditions conceptualize their own situation, and in particular the ontological status of their own condition [15]. Parvan notes that ‘the receipt of diagnosis and medical care can give patients the sense that they are ontologically diminished, or less of a human’ and this ‘may prompt them to seek ontological restoration’ by treating the disease (or associated experience of harm) as ‘a thing that exists per se ’.…”
Section: Diseases and Medical Categoriesmentioning
confidence: 99%
“…He argues that uncertainty for practitioners may be about enhancing theoretical knowledge, but for patients it is about 'knowing how to act in a taken-for-granted and largely unconscious way in a world that has become uncertain' because 'the main tool of action, the human body, no longer functions with the certainty it once had'. The paper in some ways evokes the one by Parvan [15] in that it proposes a role for practitioners in helping patients frame their situation, although in Tyreman's case the goal is not to combat substantialization but to recognize 'the uncertainty that has emerged in the patient's "habitation" and to reassure them' by restoring confidence in the body so they can act with certainty.…”
Section: Rethinking Medical Epistemologymentioning
confidence: 99%